2010
DOI: 10.4061/2010/325602
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Outcomes of Tall Cell Variant Papillary Thyroid Cancer: A Meta-Analysis

Abstract: Objective. To evaluate the prognosis of tall cell variant (TCV) compared to usual variant (UV) papillary thyroid cancer by comparing disease-related mortality and recurrence data from published studies. Methods. Ovid MEDLINE keyword search using “tall cell variant papillary thyroid cancer” was used to identify studies published in English that calculated disease-related mortality and recurrence rates for both TCV and UV. Results. A total of 131 cases of tall cell variant papillary thyroid cancer were reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
0
30
1
Order By: Relevance
“…Recent studies have suggested that the TCV should be treated with more aggressive approach. This includes total thyroidectomy followed by central compartment neck dissection and radioactive iodine ablation, regardless of tumor size (27,34). The unfavorable effect of TCV PTC on prognosis may necessitate a cautious and more aggressive approach than the one that is followed in the majority of patients with pure PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the TCV should be treated with more aggressive approach. This includes total thyroidectomy followed by central compartment neck dissection and radioactive iodine ablation, regardless of tumor size (27,34). The unfavorable effect of TCV PTC on prognosis may necessitate a cautious and more aggressive approach than the one that is followed in the majority of patients with pure PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Jalisi et al [36] reviewed a total of 131 cases of TCV and found that compared to cPTC, the combined odds ratio of recurrence and disease-related mortality for TCV is 4.5 and 14.28, respectively. As such, clinical guidelines suggest that TCV requires more aggressive clinical management [7].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional PTC (cPTC), TCV-PTCs tend to present in women and at an older age. They also have a higher rate of extrathyroidal extension and a poorer 5-year disease-specific survival than cPTC [4,5,6]. Therefore, if TCV-PTC features can be recognized in preoperative fine needle aspiration (FNA), the surgeon could be alerted to the presence of a potentially aggressive tumor so that the type and/or extent of initial surgery can be modified [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data support that tall-cell histology alone remains a significant prognostic factor independent of age, gender, and tumour size and ETE 14. A meta-analysis of 131 cases of TCV-PTC showed 4.5 times recurrence rate and 14 times greater disease-related mortality as compared with classical PTC 18. It has been suggested that the aggressive behaviour of TCV-PTC is associated with the molecular profile of these tumours 19.…”
Section: Tall Cell Variant Of Ptcmentioning
confidence: 99%